Synthesis and Characterization with Antimicrobial Activity Studies on some Transition Metal Complexes of N, O Donor Novel Schiff Base Ligand (Journal of Scientific Research, 2017)
Metal complexes of Mn(II), Fe(II), Co(II) and Cd(II) ions with Schiff base ligand 4-{(pyridin-2-ylimino)methyl}phenol derived from condensation of 2-amino pyridine with 4-hydroxybenzaldehyde was prepared. The ligand and complexes were isolated from the reaction in the solid form  and characterized by conductivity, magnetic moment, TLC, IR, UV-Visible, thermal analysis and some physical measurements. During complexation reaction with transition metal ions Schiff base act as a deprotonated tridentate ligand and IR spectra showed that N and O atoms are coordinated to the central metal atom. The observed values confirmed that the complexes have octahedral geometry. The Schiff base and its metal complexes have been found to have moderate to strong antibacterial activity.